2010
DOI: 10.3109/08860220903367528
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Tuberculosis Disease and Latent Tuberculosis Infection in Patients with End Stage Renal Disease in an Endemic Region

Abstract: Aim. Patients in chronic renal failure suffer impaired cellular immunity and have an increased risk of tuberculosis (TB). Our aim in this multicenter study was to determine the incidence of TB and to evaluate latent tuberculosis infection (LTBI) in hemodialysis patients. Methods. We retrospectively evaluated the frequency of TB in 779 dialysis patients at 13 hemodialysis centers in five different cities in Southeast Turkey. The tuberculin skin test (TST) was conducted in 733 patients to detect LTBI. Results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
1
8
2
Order By: Relevance
“…The LTB prevalence detected in this study also differs from that obtained in Minas Gerais, in which the value was 28.5% 37 , and in Turkey, in a study by Ates et al, in which the prevalence was 37.5% 38 . We emphasize that this variation may be related to the burden of TB in each region.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The LTB prevalence detected in this study also differs from that obtained in Minas Gerais, in which the value was 28.5% 37 , and in Turkey, in a study by Ates et al, in which the prevalence was 37.5% 38 . We emphasize that this variation may be related to the burden of TB in each region.…”
Section: Discussioncontrasting
confidence: 99%
“…These results align with those in the study performed in Turkey by Ates et al 38 and with the study of Ribeiro et al 41 , which took place in the interior of São Paulo and included study subjects that had been on hemodialysis for at least three years.…”
Section: Discussionsupporting
confidence: 91%
“…This has been reported before. 20,23 The rate of drug resistance to any first-line anti-TB agent (23.8%) was three times higher than the UK figures for 2013 (7.8%) 8 and twice as high as the London rate of 10.5%. 16 UK data suggest that the proportion of resistance to first-line drugs is highest in those from Eastern Europe (37%), followed by SE Asia (12.2%).…”
mentioning
confidence: 95%
“…It was found to be 6–25 times higher than in the general population, with mortality rates ranging from 17 to 75% [6]. Ates et al [8] reported that the median time between initiation of dialysis and diagnosis of TB was 11 months, which is consistent with several studies showing a high incidence of TB in the first year of dialysis attributable to poor health in general and compromised host immunity.…”
Section: Discussionmentioning
confidence: 52%
“…The incidence of TB among patients with advanced chronic kidney disease on dialysis is quite varied worldwide, ranging from 1.6 to 28% [8]. It was found to be 6–25 times higher than in the general population, with mortality rates ranging from 17 to 75% [6].…”
Section: Discussionmentioning
confidence: 99%